(3GdCTGY aj TQM GdTcd GdbWGYs - (3Ydj Hf CMeO GdfShj, CHh GdMSfs ((3GHf GdfLGTi s)
(3ChdgG (B:s
(3GdMeO ddg GdeHOF GdeYjO GdaYGd deG jQjO bGd bO GJabhG YehekG hCUMGH GdYde GdQjGVi efge NUhUkG Ydi Cf GdZQV GdCbUi ef GdYdhe GdQjGVjGJ s
(3BNQgG (B:s
(3aEf HYVkG eWGdY gPjf GdHQLjf ef eWGdY GdKdGKI GdHQhL hef HYO Cf hajfG HeG hYOfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdQjGVjGJs